2021
DOI: 10.1016/j.energy.2020.119161
|View full text |Cite
|
Sign up to set email alerts
|

In-situ synchrotron characterisation of fracture initiation and propagation in shales during indentation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The authors showed that the strain levels beneath the indentor exceeded the yield strain of dentin. The fracture development in shales was reported very recently [15]. The cracking pattern was evidenced thanks to strain fields derived from measured displacement fields.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The authors showed that the strain levels beneath the indentor exceeded the yield strain of dentin. The fracture development in shales was reported very recently [15]. The cracking pattern was evidenced thanks to strain fields derived from measured displacement fields.…”
Section: Introductionmentioning
confidence: 81%
“…In the afore-mentioned studies, various DVC schemes were considered. Most of the analyses were performed with so-called local DVC [11,12,16,19,17,18,20,14,15], in which independent sub-volumes were registered. FE-based DVC was also considered, registration residuals and strain fields were utilized to characterize cracks [10,22,13,21].…”
Section: Introductionmentioning
confidence: 99%
“…Tomography can be used for studies of mechanical properties, with the visualisation of modification in the 3D structure and propagation of the crack during indentation in static and in situ experiments [ 626 , 627 , 628 , 629 ]. Mechanical analysis has been applied in 2D, using digital image correlation on radiography images with time to characterise changes during the tooth restoration [ 318 ].…”
Section: Synchrotron (Circular Particle Accelerator)mentioning
confidence: 99%
“…The surface roughness of fractures is also greater. 130 The chemical composition of fracturing fluids can affect the dissolution and corrosion properties of rocks. Unlike water-based fracturing fluids, under high pressure, CO 2 can extract hydrocarbons from tight oil reservoir rocks, dissolve the rock matrix and minerals, 134 large water consumption and the generation of a significant amount of wastewater may lead to regional seismicity, water lock reactions, and damage to formations 135 air prone to generating fracture branching and larger surface roughness 53 poor carrying capacity of proppants 136 LPG no fluid loss, resulting in better effective fractures 136 generates a large amount of flammable propane N 2 -based can enhance the connectivity of pore and fracture networks, can quickly clean without impacting the environment, L-N 2 has a large compression coefficient and strong expansion ability, and has high elasticity 137−139 poor carrying capacity of proppants, not suitable for use in plastic formations 140 CO 2 -based good permeability, low viscosity, generates finer and more complex fracture networks, increases methane and hydrocarbon production, and favorable for carbon sequestration 77,141 poor carrying capacity of proppants, leading to significant loss and leakage, strict requirements for fracturing equipment, preparation and transportation of carbon dioxide 31 and migrate, which can effectively alter the pore structure 131 (Figure 18).…”
Section: Water Saturation Ofmentioning
confidence: 99%
“…The degree of fracture bending is greater than in hydraulic fracturing, and the morphology of fractures tends to have a three-dimensional spatial distribution. The surface roughness of fractures is also greater . The chemical composition of fracturing fluids can affect the dissolution and corrosion properties of rocks.…”
Section: Engineering Parametermentioning
confidence: 99%